What is the Status? A Systematic Review of Nutritional Status Research in Total Joint Arthroplasty. Issue 3 (September 2019) - Carli, Alberto V.; Polascik, Breanna A.; Stelmaszczyk, Kelly; Haas, Steven B.
Abstract : Malnutrition has been previously associated with impaired wound healing, slower locomotion, and poorer outcomes following elective surgery. Although academic societies dedicated to perioperative recovery have published evidence-based guidelines for malnutrition, no consensus exists within orthopedics for screening and treating malnutrition in patients undergoing total joint arthroplasty (TJA). Following PRISMA guidelines, we performed a systematic review to determine: (1) how is malnutrition defined; (2) what is the prevalence of malnutrition among patients with TJA; (3) what perioperative complications are associated with malnutrition; (4) what strategies are successful in managing malnourished patients with TJA. Eight hundred ninety-five articles were identified in the literature, with 53 fulfilling criteria for analysis. Albumin <3.5 g/dL was the most commonly used parameter to define malnutrition. Total lymphocyte count (<1500 cell/mm 3 ) and vitamin D (<20 to <12 ng/mL) were the second most commonly used parameters. Prevalence of malnutrition tended to be under 15% of primary patients with TJA in studies with over 10, 000 patients. Morbidly obese patients and patients undergoing revision TJA were found to have significantly higher rates of malnutrition. Significant associations were found with malnutrition before TJA and higher rates of postoperative length of stay, readmission, reoperation, surgical site infection, and mortality. Malnutrition and obesity were not consistently found to have a synergistic effect on complication rates. To date, no formal preoperative treatments of malnourished patients with TJA have been studied. Protein supplementation has been shown to reduced length of stay in 3 TJA studies, but supplementation strategies varied and study patients were well nourished.